Current Treatment Algorithms for Patients with Metastatic Non-Small Cell, Non-Squamous Lung Cancer - Melosky, Barbara (Frontiers in Oncology, 2017)
A number of developments have altered the treatment paradigm for metastatic non-small cell, non-squamous lung cancer. These include increasing knowledge of molecular signal pathways and new treatment options when patients progress. As a result of treatments becoming more efficacious and more personalized, survival for select groups of NSCLC patients is increasing. In this paper, three algorithms will be presented for treating patients with metastatic non-squamous, non-small cell lung cancer. These include treatment algorithms for NSCLC patients whose tumours have EGFR mutations, ALK rearrangements or wild-type/wild type tumours. As the world of immunotherapy continues to evolve quickly, a future algorithm will also be presented.